2015
DOI: 10.1155/2015/974506
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antioxidant Properties of Chitosan Films Incorporated with Cinnamon Oil

Abstract: Chitosan films (CF) with cinnamon bark oil (CO) incorporated at 0% (control), 0.25%, 0.5%, and 1.0% v/v were prepared by an emulsion method. The films were characterized based on their physical properties (solubility, water vapor permeability, optical property, and microstructure) and antioxidant properties (DPPH, ABTS, and its protective effects on human erythrocytes). The results showed that the incorporation of 0.5 and 1.0% of CO into the CF significantly decreased its solubility to 22% of the control (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 30 publications
(34 reference statements)
3
20
1
3
Order By: Relevance
“…The present result is in agreement with those of previous studies, which found that the yellow coloration in the chitosan film was intensified after addition with CEO ranged at level from 0.4% to 2% (Ojagh et al, 2010;López-Mata et al, 2015;Peng and Li, 2014). The differences in color could be ascribed to the natural yellow of essential oils (Atarés et al, 2010).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The present result is in agreement with those of previous studies, which found that the yellow coloration in the chitosan film was intensified after addition with CEO ranged at level from 0.4% to 2% (Ojagh et al, 2010;López-Mata et al, 2015;Peng and Li, 2014). The differences in color could be ascribed to the natural yellow of essential oils (Atarés et al, 2010).…”
Section: Resultssupporting
confidence: 94%
“…However, other studies showed that the incorporation of 0.5 and 1.0% of CEO into chitosan films did not cause significant difference compared with the control (Hosseini et al, 2009;López-Mata et al, 2015). Different effect on WVP of chitosan films enriched CEO in the present study and those reported in literature (Hosseini et al, 2009;López-Mata et al, 2015) may be attributed to chitosan composition and suppliers, plasticizer presence and film preparation. Figure 2 shows the mechanical properties of films.…”
Section: Figcontrasting
confidence: 74%
See 1 more Smart Citation
“…Different data were found in a study by Torrieri et al [25], who detected a rise in the water vapour transmission rate alongside increase in the amount of rosemary essential oil in chitosan films, despite a presumed boost in the hydrophobic nature of the polymer matrix due to a partial presence of lipids. Other authors [26] reported Values are expressed as mean ± standard deviation. Different letters in the same column indicate significant differences ( < 0.05).…”
Section: Physical Properties Of the Filmsmentioning
confidence: 99%
“…El principal inconveniente de las películas de quitosano es su alta permeabilidad al vapor de agua; sin embargo, esto podría reducirse mediante la adición de componentes tales como los AE (Cháfer et al, 2012). Sin embargo, la adición de AE a películas podría ser limitado debido a su volatilidad y también podría inducir efectos beneficiosos o perjudiciales en las características fisicoquímicas de la película (López-Mata et al, 2015). El propósito del presente trabajo fue evaluar las propiedades fisicoquímicas y mecánicas de películas de quitosano adicionando aceite esencial de Cymbopogon citratus.…”
Section: Introductionunclassified